2018
DOI: 10.1016/j.seizure.2018.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent experience in hybrid PET-MRI for evaluation of refractory focal onset epilepsy

Abstract: PET-MR provides additional sensitivity when used as two combined modalities for detecting possible epileptic foci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 13 publications
0
31
0
5
Order By: Relevance
“…for infantile epilepsy or infantile spasms and improves etiologic classifications and the predication of therapy efficacy [11,32]. Hybrid PET/MRIidentified 12 subtle hypometabolic areas (with fewer slices and slighter Z-score decreasing) that were overlooked by conventional visual PET analysis.…”
Section: Hybrid Pet/mri Showed Advantage In Soz Precise Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…for infantile epilepsy or infantile spasms and improves etiologic classifications and the predication of therapy efficacy [11,32]. Hybrid PET/MRIidentified 12 subtle hypometabolic areas (with fewer slices and slighter Z-score decreasing) that were overlooked by conventional visual PET analysis.…”
Section: Hybrid Pet/mri Showed Advantage In Soz Precise Localizationmentioning
confidence: 99%
“…With PET/MRI guidance, we were able to localize hypometabolic epileptic areas more precisely, and therefore could reduce the number of SEEG electrodes needed. The number of SEEG electrodes was reduced to 7.07 ± 1.85 (range, [6][7][8][9][10][11][12][13][14] electrodes for each patient, which had two main advantages: reduced brain injury and decreased patient financial burdens. Hybrid PET/MRI helped to navigate SEEG to localize the SOZ in 35 patients (83.33 %) and showed the same SOZ localization with SEEG in 27 patients (64.29 %), values that were defined as being concordant.…”
Section: Utility Of Hybrid Pet/mri In Navigating Seeg Electrode Implamentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies by Oldan and colleagues and Shin et al evaluated the utility of hybrid PET-MRI in evaluation of refractory focal epilepsy, and they noted that PET-MRI fusion was able to identify additional lesions better than MRI alone, including lesions seen only retrospectively on MRI after detection on PET. 15,16 Their data suggest that PET-MR has the most utility in widening the range of possible targets rather than confirming a site of resection, and this may help predict areas of interest for invasive monitoring to guide surgical resection. With varied results on the predictive value of PET-CT and PET-MRI in postoperative patients, more studies are needed to help understand fully the role of this new imaging technology.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, hybrid PET/MRI relies on MR-based attenuation correction (MRAC) for PET reconstruction instead of CT-based AC used in PET/CT, which is the current clinical standard for FDG-PET imaging in epilepsy. While some studies show that traditional MRAC approaches can produce small bias in quantitative PET due to inadequate modeling of bone (Larsson et al 2013;Andersen et al 2014), recent reports have revealed that these MRAC biases do not significantly impact the clinical diagnosis of FDG-PET readings in epilepsy (Paldino et al 2017;Oldan et al 2018). Nevertheless, alternative MRAC methods have been proposed to reduce potential bias in reconstructed PET (Ladefoged et al, 2017).…”
Section: Discussionmentioning
confidence: 99%